The Influence of Contextual Teaching and Learning Methods and Emotional Intelligence Toward Vocational High School Students' Entrepreneurship Learning Outcomes - Kafyanti Nurmeli; Idris Idris (STAI Hubbulwathan Duri, 2024)
This study examines the effects of the Contextual Teaching and Learning (CTL) method and emotional intelligence on entrepreneurship learning outcomes in vocational high school students. Given the growing importance of entrepreneurial skills in education, understanding how teaching methods and emotional factors contribute to student success is crucial. The research employs a causative approach, focusing on Class XI students at a public vocational high school in Padang Panjang. Primary data were collected through questionnaires distributed to students, capturing their learning experiences with the CTL method and self-reported levels of emotional intelligence. Data analysis was conducted using SPSS to evaluate relationships and interaction effects between variables. The analysis reveals that the CTL method significantly improves learning outcomes for students in entrepreneurship. Emotional intelligence also has a positive effect on these outcomes, with students demonstrating higher emotional intelligence achieving better results. Notably, an interaction effect was found between the CTL method and emotional intelligence, suggesting that students benefit most when both are present. These findings highlight the value of combining contextual teaching methods with emotional intelligence to maximize learning outcomes. The interaction effect emphasizes that integrating these elements can create a more conducive learning environment for developing entrepreneurial skills. The study concludes that both the CTL method and emotional intelligence play critical roles in enhancing entrepreneurship education among vocational students. Schools are encouraged to adopt CTL methods while fostering emotional intelligence to improve student success in entrepreneurial competencies.